Avoidable deficiencies in the delivery of health care to children with meningococcal disease. Issue 5 (September 1998) - Nadel, S; Britto, J; Booy, R; Maconochie, I; Habibi, P; Levin, M
Abstract : OBJECTIVES: It is apparent that delays and inadequate or inappropriate management occur frequently and may contribute to the continued high mortality seen in meningococcal disease. An attempt has been made to define the major sources of delay or inappropriate treatment. METHODS: A prospective, descriptive study of children with meningococcal disease referred to a tertiary centre paediatric intensive care and infectious disease unit. Definitions of optimal care were established at three stages: parental; general practitioner (GP)/accident and emergency (A&E) department; and hospital. Duration of symptoms and management were recorded from direct questioning of parents and carers, and from hospital records. RESULTS: 54 consecutive children with meningococcal disease were recruited to the study. Delayed parental recognition occurred in 16 children. GPs correctly diagnosed 19 of 35 children. Delay of 2.5-21 hours occurred in those who were incorrectly diagnosed. Two of 15 children who presented to the A&E department with specific features were incorrectly diagnosed. Hospital treatment was suboptimal in 71%. Shock was not recognised or treated in 50%, 20% of children had unnecessary lumbar punctures. Time from illness onset to treatment was longer in fatal disease (median 18.3, range 8-24 hours), compared with survivors (median 12, range 2-48 hours; p < 0.01, Mann-Whitney U test). CONCLUSION: Suboptimal treatment in meningococcal disease is due to failure of parents, GPs, and hospital doctors to recognise specific features of the illness. Improvement by public education and better training of clinicians in recognition, resuscitation, and stabilisation of seriously ill children.